2019
DOI: 10.1007/s00228-019-02673-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of itraconazole, food, and ethnic origin on the pharmacokinetics of ivosidenib in healthy subjects

Abstract: Purpose To assess the effect of ethnicity, food, and itraconazole (strong CYP3A4 inhibitor) on the pharmacokinetics of ivosidenib after single oral doses in healthy subjects. Methods Three phase 1 open-label studies were performed. Study 1: Japanese and Caucasian subjects received single doses of 250, 500, or 1000 mg ivosidenib (NCT03071770). Part 1 of study 2 (a two-period crossover study): subjects received 500 mg ivosidenib after either an overnight fast or a high-fat meal. Subjects received 1000 mg ivoside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 21 publications
(26 reference statements)
2
19
0
Order By: Relevance
“…10 The covariate effects of moderate and strong CYP3A4 inhibition with concomitant voriconazole, fluconazole, and posaconazole had a moderate effect on ivosidenib exposure based on AUC. Although the detailed dose, regimen, and compliance for these concomitant medications were unknown in this study, the magnitude of strong CYP3A4 inhibition predicted from this analysis was broadly similar to the results from a dedicated clinical pharmacology study of the effect of the strong CYP3A4 inhibitor itraconazole on ivosidenib exposure (1.69-fold change in plasma AUC in healthy participants after multiple doses of ivosidenib) 15 and a physiologically based PK model prediction (1.44-fold change in plasma AUC in patients with AML after multiple doses of ivosidenib in the presence of itraconazole). 12 Thus, co-administration of strong CYP3A4 inhibitors with ivosidenib requires an ivosidenib dose reduction.…”
Section: Discussionsupporting
confidence: 70%
“…10 The covariate effects of moderate and strong CYP3A4 inhibition with concomitant voriconazole, fluconazole, and posaconazole had a moderate effect on ivosidenib exposure based on AUC. Although the detailed dose, regimen, and compliance for these concomitant medications were unknown in this study, the magnitude of strong CYP3A4 inhibition predicted from this analysis was broadly similar to the results from a dedicated clinical pharmacology study of the effect of the strong CYP3A4 inhibitor itraconazole on ivosidenib exposure (1.69-fold change in plasma AUC in healthy participants after multiple doses of ivosidenib) 15 and a physiologically based PK model prediction (1.44-fold change in plasma AUC in patients with AML after multiple doses of ivosidenib in the presence of itraconazole). 12 Thus, co-administration of strong CYP3A4 inhibitors with ivosidenib requires an ivosidenib dose reduction.…”
Section: Discussionsupporting
confidence: 70%
“…Ivosidenib has a moderate food effect on C max , which is attributed to its solubility‐limited absorption 3 . Participants with hepatic impairment may have changes in gastrointestinal environment, such as bile salt content and phospholipids, which influence the solubility of the drug and thus reduce ivosidenib absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies to date have shown that ivosidenib is readily absorbed and slowly eliminated after a single dose in healthy participants and in patients with advanced mutant IDH1 solid and hematologic malignancies 1,3,4 . In vitro and in vivo studies identified the liver as a primary organ involved in the clearance of ivosidenib.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A steady state was achieved within 14 days of administration. A single-dose food effect study in healthy subjects indicated that a high-fat meal increased the mean peak plasma concentration by 98% [47]. Therefore, it is advised that ivosidenib should not be administered with a high fat meal.…”
Section: Pharmacokinetics and Metabolismmentioning
confidence: 99%